2011
DOI: 10.1007/s11745-011-3555-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Improves Reverse Cholesterol Transport in Cholesteryl Ester Transfer Protein Transgenic Mice

Abstract: We analyzed the effect of a 6-week aerobic exercise training program on the in vivo macrophage reverse cholesterol transport (RCT) in human cholesteryl ester transfer protein (CETP) transgenic (CETP-tg) mice. Male CETP-tg mice were randomly assigned to a sedentary group or a carefully supervised exercise training group (treadmill 15 m/min, 30 min sessions, five sessions per week). The levels of plasma lipids were determined by enzymatic methods, and the lipoprotein profile was determined by fast protein liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
3
21
0
14
Order By: Relevance
“…These results are consistent with Kraus and Slentz [56] and Rocco et al [59] to report that exercise increased the HDL -cholesterol fraction and prevented the development of atherosclerosis.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with Kraus and Slentz [56] and Rocco et al [59] to report that exercise increased the HDL -cholesterol fraction and prevented the development of atherosclerosis.…”
Section: Discussionsupporting
confidence: 92%
“…Kamani et al [72] found a significant decrease in mean PCSK9 levels and mean LDL-C levels in volunteers after 3 months exercise, and concluded that daily exercise is independently associated with a decrease in PCSK9 levels over time. Rideout et al [73] used C57BL/6 mice as a model, and feed them with high-fat diet, then make them do aerobic exercise. After 8 weeks, the levels of PCSK9 mRNA and sterol regulatory element binding protein 2 (SREBP2) were increased significantly in mice with high-fat diet and exercise training, 1.9 and 1.8 times higher than those only with high-fat diet respectively.…”
Section: Aerobic Exercise With Lipids and Lipoproteinsmentioning
confidence: 99%
“…However, a study by our group did not find any impact of voluntary wheel running on in vivo macrophage RCT in wild-type mice, even though cholesterol efflux from macrophage foam cells towards plasma of exercising mice in vitro was significantly increased [93]. On the other hand, macrophage RCT was higher in exercising human CETP transgenic mice when compared with sedentary controls [94]. This beneficial effect of regular exercise training on RCT was at least in part ascribed to a raise in plasma HDL cholesterol and an enhanced hepatic uptake of cholesterol through elevated LDL receptor protein expression [94].…”
Section: What Are the Factors Influencing Multiple Steps In The Revermentioning
confidence: 99%